2018
DOI: 10.1080/13607863.2018.1531375
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of psychological distress and sleep quality in former family caregivers of people with dementia

Abstract: Objectives:The stress-related psychological symptoms experienced by informal family caregivers do not always improve or resolve after the death of the care recipient. The purpose of this study was to explore the independent associations of sociodemographic variables, personality and coping, environmental variables, and caregiver guilt with the sleep quality and psychological distress of former family caregivers of individuals with dementia following care recipient's death. Method:A cross-sectional, correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 57 publications
2
30
0
Order By: Relevance
“…This study is a secondary analysis of the recruitment methods and completeness of data collected from former family caregivers of persons with dementia. The parent study aim was to explore associations between caregiver characteristics, psychological distress, and sleep quality (Corey et al, in press). Participants in the parent study were eligible for the study if they: were age 18 or older, were English speaking, provided informal, unpaid care to a person with dementia for at least six consecutive months prior to the care recipient’s death, and if the care recipient was deceased.…”
Section: Methodsmentioning
confidence: 99%
“…This study is a secondary analysis of the recruitment methods and completeness of data collected from former family caregivers of persons with dementia. The parent study aim was to explore associations between caregiver characteristics, psychological distress, and sleep quality (Corey et al, in press). Participants in the parent study were eligible for the study if they: were age 18 or older, were English speaking, provided informal, unpaid care to a person with dementia for at least six consecutive months prior to the care recipient’s death, and if the care recipient was deceased.…”
Section: Methodsmentioning
confidence: 99%
“…A future study with a larger group of participants should continue to assess the effects on well-being outcomes and analyse whether this type of intervention is more suitable for certain subgroups of individuals with experience of informal caregiving. Previous research on former caregivers in general suggests that the post-caregiving experiences and outcomes may depend on, amongst other things, the characteristics of the past caregiving situation such as pre-loss levels of social support [ 8 , 9 ], pre-loss levels of depressive symptoms [ 7 , 9 ], and whether the care recipient died in the preferred setting [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the participants reported high scores on well-being is also in line with previous studies on post-caregiving health in general suggesting that for most former caregivers, adverse effects associated to intensive caregiving diminish with time [ 8 , 9 , 45 ]. Still, studies have also found that for some post-caregivers, negative health effects [ 7 , 8 , 9 , 44 , 45 ] such as insomnia, depressive symptoms, and feelings of guilt may prevail, even for as long as up to 10 years [ 7 ]. The specific needs of such vulnerable former caregivers should be further studied and met in interventions where they are the end-users.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations